Corrosion Behavior of 304 Stainless Steel with Two Kinds of Different Surface Treatments in Wenchang and Wuhan Atmospheric Environment - CHEN Hao, ZHOU Xue - jie, WU Jun, ZHENG Peng - hua, WANG Yi - pin (Cailiao Baohu, 2021)
For studying the corrosion behavior and corrosion mechanism of 304 stainless steel samples after two kinds of surface treatments in Wenchang and Wuhan, the samples of Wenchang and Wuhan after two years exposure test were analyzed by electrochemical test, body microscope and molecular dynamics simulation. Exposure test results showed that the corrosion of 304 stainless steel in Wenchang was more serious than that in Wuhan. Electrochemical test results indicated that 304 stainless steel still had good corrosion resistance in Wuhan area, and the calculated data results presented the passivation film of BA surface sample was more stable and possessed a smaller number of surface - active pitting corrosion. Furthermore, the results of molecular dynamics simulation showed that Cl - was the main particle that interacted with the sample surface during the corrosion process, and the diffusion process of chloride ion was inhibited by Cr2O3 oxide film.